A case report on pheochromocytoma mimicking as fulminant myocarditis—a diagnostic challenge - Cheng, Yanwei; Ding, Ning; Wang, Longan; Qin, Lijie (Frontiers in Cardiovascular Medicine, 2024)
We present an exceptional case of a 53-year-old female, initially misdiagnosed with fulminant myocarditis, but later correctly diagnosed with pheochromocytoma. The presentation of the patient included a spectrum of symptoms such as headache, chest discomfort, palpitations, and dyspnea, following the intake of Domperidone. Two weeks prior to admission, the patient had experienced episodes of diarrhea and a low-grade fever.Unresolved symptoms and an unmanageable surge in blood pressure despite comprehensive fulminant myocarditis treatment prompted further investigation. The discovery of an adrenal mass via a CT scan and subsequent biochemical tests led to the confirmation of pheochromocytoma. Implementation of alpha-blockade therapy and a successful laparoscopic adrenalectomy resulted in significant clinical improvement. This case underscores the diagnostic intricacies of pheochromocytoma and highlights the need for vigilance when faced with severe, unresponsive cardiovascular symptoms.